2010
DOI: 10.1002/hipo.20712
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of tau phosphorylation in adult hippocampal neurogenesis

Abstract: An increased hippocampal neurogenesis has been observed in Alzheimer disease (AD), the most common neurodegenerative disorder characterized with accumulation of β-amyloid (Aβ) and hyperphosphorylated tau (p-tau). Studies in transgenic mouse models suggest that the amyloidosis suppresses adult neurogenesis. Although emerging evidence links tau to neurodevelopment, the direct data regarding tau phosphorylation in adult neurogenesis is missing. Here, we found that the immature neurons, identified by doublecortin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 48 publications
3
57
1
1
Order By: Relevance
“…One of the tau isoforms, Tau-3R, is expressed by adult newborn neurons (Fuster-Matanzo et al, 2012). Interestingly, phosphorylated tau + cells are co-expressed with two markers of newborn neurons, DCX and NeuroD, in both a temporal and spatial fashion (Fuster-Matanzo et al, 2009;Hong et al, 2010). It is thus possible that more may be learned about the alterations in neurogenesis in AD by using tau-based mouse models over amyloid-based models given the need for tau expression under normal physiological conditions.…”
Section: Alterations In Hippocampal Neurogenesis In Ad Mouse Modelsmentioning
confidence: 99%
“…One of the tau isoforms, Tau-3R, is expressed by adult newborn neurons (Fuster-Matanzo et al, 2012). Interestingly, phosphorylated tau + cells are co-expressed with two markers of newborn neurons, DCX and NeuroD, in both a temporal and spatial fashion (Fuster-Matanzo et al, 2009;Hong et al, 2010). It is thus possible that more may be learned about the alterations in neurogenesis in AD by using tau-based mouse models over amyloid-based models given the need for tau expression under normal physiological conditions.…”
Section: Alterations In Hippocampal Neurogenesis In Ad Mouse Modelsmentioning
confidence: 99%
“…However, the relationship between neurogenesis and phosphorylated tau protein received little attention. Our recent studies have shown that tau phosphorylation by GSK-3 can stimulate adult hippocampal neurogenesis [15]. In addition, another laboratory has also reported increased neurogenesis during tau hyperphosphorylation in THY-Tau22 mice [16].…”
Section: Introductionmentioning
confidence: 95%
“…Inhibition of GSK-3b was associated with a reduction in axon growth and a dramatic increase in growth cone size [29]. Recently we have demonstrated that activated GSK-3b can stimulate hippocampal neurogenesis in adult rat brain [15], but we still know little about the influence of GSK-3b on the SVZ neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Less studied, however, are the direct effects on adult hippocampal neurogenesis of proteins that, as tau, regulate the morphogenesis and functional integration of new neurons (Bullmann et al, 2007;Fuster-Matanzo et al, 2012;Hong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%